The impact of first-person avatar customization on embodiment in immersive virtual reality - Gonzalez-Franco, Mar; Steed, Anthony; Berger, Christopher C.; Tajadura-Jiménez, Ana (Frontiers in Virtual Reality, 2024)
In virtual reality (VR), users can embody a wide variety of avatars; from digital replicas of themselves, through diverse human body styles and appearance to non-humanoid representations. While choosing a body to inhabit is part of what makes VR such an engaging experience, various studies have shown how embodiment may change the way we perceive ourselves and others both inside and outside VR. In our study, we explored whether first-vs. third-person avatar customization would lead to changes in embodiment. Further, participants were embodied in larger-sized avatars, based on the hypothesis that embodiment would lead to a change in implicit bias towards larger-sized people. Our results show that third-person avatar customization led to a decrease of perceived embodiment of the larger-sized avatar, and that, on the contrary, higher embodiment was associated with a reduction of implicit biases towards larger-sized people in the first-person avatar customization mode. These findings suggest that third-person avatar customization leads to reduced feelings of embodiment, while first-person avatar customization may support more radical body changes.